2007
DOI: 10.1177/0340035207086057
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy in Practice: engaging public library workers in rural South Africa

Abstract: Mpumalanga Provincial Library Services offers public library services in a largely rural "new" province that was created in 1996 after the elections of 1994. Many of the libraries are in isolated areas and have to meet the very diverse needs of their communities. This paper reports the results of an information literacy intervention designed for public library workers in this province. The campaign, a first of its kind in Mpumalanga (and South Africa), gave public library workers the opportunity to develop the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Public libraries are places of informal lifelong learning for all (McNicol and Dalton, 2003), and have a key role to play in democratic societies by engaging users with information critically, and encouraging active creation of information (Hall, 2010). Yet, there is surprisingly little emphasis given to the public library in the IL literature (Harding, 2008), and studies including public librarians reveal a lack of preparedness and confidence for IL provision (Bruce and Lampson, 2002; de Jager and Nassimbeni, 2007; Hart, 2006; Julien and Hoffman, 2008). These studies also find that CT is considered an important aspect of IL by public librarians, but at the same time show a strong emphasis on the evaluation of sources rather than their content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Public libraries are places of informal lifelong learning for all (McNicol and Dalton, 2003), and have a key role to play in democratic societies by engaging users with information critically, and encouraging active creation of information (Hall, 2010). Yet, there is surprisingly little emphasis given to the public library in the IL literature (Harding, 2008), and studies including public librarians reveal a lack of preparedness and confidence for IL provision (Bruce and Lampson, 2002; de Jager and Nassimbeni, 2007; Hart, 2006; Julien and Hoffman, 2008). These studies also find that CT is considered an important aspect of IL by public librarians, but at the same time show a strong emphasis on the evaluation of sources rather than their content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have shown that public libraries in other countries are also experiencing a similar problem. For example, non-professional librarians were also managing public libraries in Namibia (Hamwaalwa, 2015), in Slovac Republic (Papcunova et al, 2017), in South Africa (De Jager and Nassimbeni, 2007), and Uganda (Caro, 2019). Those local and international studies have emphasized the importance of the presence of professional librarians in public libraries.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…Julien [41] indicated that Canadian public libraries were approaching IL instruction and defined the factors that limit IL implementation. De Jager and Nassimbeni [42] stated that public library staffs have indeed made a difference in the IL of their respective communities. Koltay [43] examined the role of IL and digital literacy under the circumstances and challenges of the Web 2.0 environment, and indicated that users require literacies similar to services traditionally offered by academic, special and public libraries.…”
Section: Implication Of Digital Information Literacy In Public Librariesmentioning
confidence: 99%